2015
DOI: 10.4028/www.scientific.net/msf.821-823.745
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Interface State Density from Subthreshold Slope of MOSFETs at Low Temperatures (≥ 10 K)

Abstract: We have evaluated interface state density (DIT) for EC−ET > 0.00 eV from the subthreshold slope deterioration of MOSFETs at low temperatures. We have compared two n-channel MOSFETs on the C- and a-faces with the gate oxide formed by pyrogenic oxidation followed by annealing in H2. The peak field-effect mobility (µFE,peak) for the C-face MOSFET was 57 cm2V-1s-1 at 300 K, which is lower than the half of 135 cm2V-1s-1 for the a-face MOSFET. We have shown that DIT very close to EC can well explain why µFE for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 9 publications
(12 reference statements)
1
14
0
Order By: Relevance
“…However, as indicated by the spread of the two lines, the correlation between µ FE,peak (300 K) and the interface state density became weaker in the order of D IT,∆I (0.00 eV), N T,∆I , and D IT,∆I (0.18 eV). The correlation with D IT,∆I (0.18 eV) is consistent with the correlation with D IT (C − ψ S , 0.2 eV), 12 and µ FE,peak (300 K) for the a-face MOSFETs were higher than those on the other faces at the equivalent D IT,∆I (0.18 eV), which indicates that D IT at about 0.2 eV is insufficient as the factor that deteriorates µ FE for the Si-and C-face MOSFETs when compared with that for the a-face MOSFETs. Therefore, we conclude that D IT near E C is the most critical factor for µ FE,peak (300 K) and that µ FE for the Si-and C-face MOSFETs is lower than that for the a-face MOSFETs because of D IT at the energy very near to the conduction band edge.…”
Section: -7supporting
confidence: 68%
See 3 more Smart Citations
“…However, as indicated by the spread of the two lines, the correlation between µ FE,peak (300 K) and the interface state density became weaker in the order of D IT,∆I (0.00 eV), N T,∆I , and D IT,∆I (0.18 eV). The correlation with D IT,∆I (0.18 eV) is consistent with the correlation with D IT (C − ψ S , 0.2 eV), 12 and µ FE,peak (300 K) for the a-face MOSFETs were higher than those on the other faces at the equivalent D IT,∆I (0.18 eV), which indicates that D IT at about 0.2 eV is insufficient as the factor that deteriorates µ FE for the Si-and C-face MOSFETs when compared with that for the a-face MOSFETs. Therefore, we conclude that D IT near E C is the most critical factor for µ FE,peak (300 K) and that µ FE for the Si-and C-face MOSFETs is lower than that for the a-face MOSFETs because of D IT at the energy very near to the conduction band edge.…”
Section: -7supporting
confidence: 68%
“…In contrast, we showed that D IT , when evaluated on the basis of the subthreshold slope (S) of a MOSFET, is consistent with D IT evaluated by the C−ψ S method, 12 which indicates that the subthreshold slope deterioration of 4H-SiC MOSFETs is caused by the interface states. 9,[14][15][16] Because the Fermi energy (E F ) at the interface that corresponds to the subthreshold region approaches E C with decreasing temperature, D IT at energies nearer E C can be evaluated from the subthreshold slope at lower temperatures.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…A key problem is the high density of so called near-interface traps (NITs) detected at the SiO 2 /4H-SiC interface with energy levels near the SiC conduction band edge that limit the electron channel mobility. [3][4][5][6] Currently thermal oxides grown or annealed in NO or N 2 O are the mainstream dielectrics but more reduction in NITs is needed. 7 Other large bandgap dielectrics such as AlN, Al 2 O 3 and HfO 2 have also been investigated.…”
Section: Introductionmentioning
confidence: 99%